Willingness for Land Transfer and Coupling Coordination Analysis in Poverty Alleviation Resettlement Areas: A Sustainable Development Perspective - Zhijie Cao; Lingzhi Yan; Kexin Zhou; Ming Lei (Land)
This study focuses on the land transfer intentions of migrants and surrounding villagers in the SZ resettlement area of BS City, Guangxi. It systematically analyzes the coupling coordination relationship between migrants’ land transfer-in intentions and the land transfer-out intentions of surrounding villagers, verifying the practical value of the “Shared Land Resource Model” in the resettlement area and its surroundings. The study yields the following key conclusions: (1) there is a strong coupling between the land demand intentions of migrants and the land supply intentions of surrounding villagers, yet the actual coordination in the transfer process is limited, which constrains resource allocation efficiency and prevents land transfer from fully utilizing shared resources; (2) in the evaluation of migrants’ land transfer-in intentions, external environmental factors have the greatest influence (with a weight coefficient of 0.7877), while individual characteristics (0.0486) and psychological characteristics (0.0593) have relatively low weight coefficients, indicating that migrants primarily rely on government policy support and lack internal motivation; (3) the land transfer-out intentions of surrounding villagers are most affected by farmland resource endowment (weight coefficient of 0.3284), indicating that the quality and quantity of land resources are key factors affecting villagers’ transfer-out willingness, while individual endowment factors have the smallest impact (weight coefficient of 0.1220). Three recommendations are proposed: stimulating migrants’ intrinsic motivation to enhance livelihood autonomy, protecting villagers’ land rights to increase transfer participation, and building a systematic land resource sharing model to promote sustainable resource allocation. This study provides theoretical support for optimizing the land transfer mechanism in resettlement areas, aiming to improve land use efficiency, support the livelihood transition of migrants, and offer practical insights for land management planning in poverty alleviation and resettlement projects in other countries.